Multi-omics analysis of Iris sanguinea with distinctive flower colors provides insights into petal coloration - Guiling Liu; Huijun Liu; Gongfa Shi; Nuo Xu; Zhaoqian Niu; Lei Wang; Ruiyang Zhao; Ling Wang; Lijuan Fan (Horticultural Plant Journal)
Iris sanguinea Donn ex Horn. is a common perennial ornamental herb in Northeast China due to its strong cold-resistance capacity. In this study, integrative analyses of metabolomics and transcriptomics data were performed on five cultivars of I. sanguinea with varying petal colors to elucidate the molecular basis underlying petal pigmentation. The metabolomics data revealed that a total of five major anthocyanins were responsible for petal pigmentation in I. sanguinea. While two delphinidin-3-O-glucoside derivatives contributed to blue coloration in petals, two petunidin-3-O-glucoside and cyanidin-3-O-rutinoside derivatives exhibited significantly higher abundances in the deep pink petals. In addition, transcriptomics revealed a gradual increase in the expression of a large set of genes involved in flavonoid and anthocyanin biosynthesis pathways, corresponding to the varying levels of anthocyanin content among cultivar petals. Integrated metabolomics and transcriptomics analysis further led to the discovery of molecular modules controlling petal pigmentation, in which an R2R3 MYB transcription factor IsMYBL1 was found to be associated with the accumulation of key anthocyanin derivatives, it localized to the nucleus. The regulatory role of IsMYBL1 in anthocyanin accumulation has been validated through overexpressing in tobacco and knockdown in I. sanguinea using an improved virus-induced gene silencing (VIGS) approach. Finally, BiFC and Y2H showed that IsMYBL1 interacts with IsEGL3 and IsTTG1 to activate the expression of genes involved in anthocyanin biosynthesis, Yeast one-hybrid, dual-luciferase assays, showed that IsMYBL1 significantly increased anthocyanin contents in I. sanguinea by promoting the expression of IsANS, thereby promoting anthocyanin accumulation. Taken together, our study has provided a comprehensive molecular profiling of petal coloration in I. sanguinea and revealed key gene/metabolite networks that determine petal pigmentation.